2019
DOI: 10.3390/ijms20143503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on In Vitro and In Vivo Models of Diabetic Retinophathy: A Systematic Review

Abstract: A large number of preclinical studies suggest the involvement of resveratrol in the prevention and treatment of eye diseases induced by oxidative stress and inflammation. We tested the hypothesis that resveratrol influences many pathways of in vitro and in vivo models of diabetic retinopathy through a systematic literature review of original articles. The review was conducted in accordance with the PRISMA guidelines. A literature search of all original articles published until April 2019 was performed. The ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…Resveratrol is a natural polyphenol found in the skin of grapes, blueberries, raspberries, and peanuts, exhibiting anti-oxidative, anti-inflammatory, anti-apoptotic, and anti-aging effects [ 248 ]. At present, there has been no report on detrimental effects of resveratrol in both experimental animal and human studies, making it an attractive candidate for therapeutic use [ 249 ]. Li et al reported that resveratrol was effective to prevent ROS generation in DR via inhibition of the ROS/AMPK/Sirt1/PGC-1α pathway [ 250 ].…”
Section: Therapeutic Strategies To Reduce Oxidative Stressmentioning
confidence: 99%
“…Resveratrol is a natural polyphenol found in the skin of grapes, blueberries, raspberries, and peanuts, exhibiting anti-oxidative, anti-inflammatory, anti-apoptotic, and anti-aging effects [ 248 ]. At present, there has been no report on detrimental effects of resveratrol in both experimental animal and human studies, making it an attractive candidate for therapeutic use [ 249 ]. Li et al reported that resveratrol was effective to prevent ROS generation in DR via inhibition of the ROS/AMPK/Sirt1/PGC-1α pathway [ 250 ].…”
Section: Therapeutic Strategies To Reduce Oxidative Stressmentioning
confidence: 99%
“…PDR patients had lower levels of TAC in the vitreous and aqueous humor, but not in the blood, compared with nonproliferative diabetic retinopathy patients. These results suggest that the development of diabetic retinopathy is associated with high-level oxidative stress and diminished antioxidant defenses [ 36 , 37 ]. This report encourages the further investigation of the vitreous body.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing mainly on DR, resveratrol has a protective role involving OS-induced apoptosis by reducing intracellular ROS through the AMPK/Sirt1/PGC-1α pathway [175] and, like the other polyphenols, is as an activator of Nrf2 [173]. In in vitro studies with human retinal pigment epithelial cells (ARPE-19 cells), resveratrol showed an inhibitory effect on inflammatory cytokines such as IL-6 and IL-8 [176], and in preclinical studies, resveratrol also inhibited VEGF through yet another pathway, by increasing the activity of paraoxonase 1 (PON1) which is involved in protecting endothelial cells [177] and inhibiting the VEGF expression [178]. Unlike other nutraceuticals, resveratrol exhibits a biological property to act on a more directed manner against apoptosis, mainly on Müller cells by upregulating the microRNA-29b, and so downregulating specific protein 1 expression [179] and directly inhibiting caspase-8 and caspase-3 as seen in Figure 2 [180].…”
Section: Polyphenols: Anthocyanins and Resveratrolmentioning
confidence: 99%